2020
DOI: 10.5433/1679-0359.2020v41n6supl2p2911
|View full text |Cite
|
Sign up to set email alerts
|

Growth of canola hybrids resistant and sensitive to herbicides

Abstract: Plant growth analysis is useful for determining adequate management practices and exploring the maximum yield potential of cultivars or hybrids. Canola hybrids with resistance to herbicides have been studied and registered for Brazilian conditions, as they improve weed management in canola crops. This study evaluated the growth of canola hybrids resistant to triazine or imidazolinone herbicides compared to a sensitive hybrid. The experiment was conducted using a completely randomized design, with four replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Greenhouse trials have shown that when = CL varieties are grown, similar yields are achieved as when non-CL varieties are used. A yield depression in the field due to the variety is therefore not to be expected [12]. The development of new herbicides with new modes of action is not expected in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…Greenhouse trials have shown that when = CL varieties are grown, similar yields are achieved as when non-CL varieties are used. A yield depression in the field due to the variety is therefore not to be expected [12]. The development of new herbicides with new modes of action is not expected in the near future.…”
Section: Introductionmentioning
confidence: 99%